3,4-Dihydropyrimidine-2(1H)-one/thione Derivatives as Anti-inflammatory and Antioxidant Agents: Synthesis, Biological activity, and Docking Studies - Nawal, Nandita; Chawla, Pooja A; Virendra, Sharma Arvind; Chawla, Viney (Current Organic Chemistry, 2025)
A series of sixteen new 4-(substituted phenyl)-6-(substituted phenylamino)-3,4-dihydropyrimidine-2(1H)-one/thione derivatives have been synthesized in two-step reaction. In the first step, chalcones (I1-I6) were obtained, and in the second step, these chalcones were reacted with urea and thiourea in the presence of potassium hydroxide to obtain the corresponding pyrimidinones and thiopyrimidinones. The progress of reaction was monitored by means of TLC (visualized it in Iodine chamber), The structures of the synthesized compounds 4-(substituted phenyl)-6-(substituted phenylamino)-3,4-dihydropyri-midine-2(1H)-ones/thione derivatives were investigated by IR, mass, 1H-NMR spectral and elemental analysis. The title compounds were evaluated for anti-inflammatory and antioxidant activity. Anti-inflammatory activity in vivo was carried out using the carrageenan-induced rat-paw edema method and compared with standard drug diclofenac sodium. Antioxidant activity was measured using the DPPH, FRAP, and hydrogen peroxide (H2O2) method and compared with standard ascorbic acid. Electron-donating groups showed better antioxidant activity than electron-withdrawing ones in both series. All the compounds exhibited good to moderate activity. Compound DHPM8 showed better antioxidant activity, and compound DHPM6 exhibited better anti-inflammatory activity, while compound DHPM11 showed minimum antioxidant as well as anti-inflammatory activities than other compounds. To better understand, molecular docking studies were performed. The molecular docking studies revealed that all synthesized compounds showed good receptor binding interaction in which compound DHPM9 had the highest docking score of 9.8 due to interaction with CYS36, PRO153, TYR130, GLY45, LEU152, ARG469, LYS468, and GLU465.
Keywords: hydrogen peroxide